PENGARUH GAYA MENGAJAR GURU, DISIPLIN BELAJAR, DAN TEMAN SEBAYA TERHADAP PRESTASI BELAJAR - Al Khumaero, Lathifah; Arief, Sandy (Economic Education Analysis Journal, 2017)
The purpose of that study was to determine the influence of teachers’ teaching method, learning disciplines, and peers on learning achievement. Population in this research are students of XI IPS SMA Negeri 1 Bawang in the academic year 2016/2017. The sample of this research was 144 students using saturated sample technigue. The method is used to collect data is quetionnaire. Data analysis method used arethe percentage descriptive analysis and inferential statistics. The results showed that the teachers’ teaching method, learning disciplines, and peers simultaneously affect the learning achievement, Partially, the influence of teachers’ teaching method, learning disciplines, and peers have a positive effect on learning achievement. The results of adjusted R2 showed the presence of the relationship between Teachers' teaching method, learning disciplines, and peers against the learning achievementas much as 51 %.Suggestions related to the results of this study are: Economics teachers are expected to have an interesting teaching method so that students are not bored during learning process. In addition, students are also expected to improve their learning disciplines both at home and at school. They are also expected to have peers who motivate them to learn a lot consistenty for gaining better achievement.